Proceso de elaboración de harina de zapallo (Cucúrbita máxima). - Ramos Cedeño, Martha Cecilia (2011)
The objective of this research work was the process of making flour pumpkin, this research was done in the workshop of unit operations of the Faculty of Engineering of the State Technical University Quevedo, located at Av Quito via Santo Domingo, Province of Rivers, whose location is from 1 ° 2'30''southern latitude and 79 º 28'30''west at a height of 74 meters. With a duration of 120 days. According to bibliographic data obtained, we conducted a literature review of the vegetable (squash), it was used for raw material quality characteristics. For the development of this work, a design factory A x B x C with eight treatments and three replicates, the statistical test used was Tukey at 5% probability. Study factors were: A (state of maturity of the pumpkin), B (drying temperature), C (drying time). The variables analyzed were: sensory analysis in the pumpkin (color, smell and appearance), physical - chemical analysis in the flour (moisture, ash, protein, fat, fiber, pH, acidity and brix) and material balance for the best treatment provided by the response of the physical and chemical analysis. During the process of flour, made the respective reception and selection of raw materials, followed by washing and disinfection, then proceeded to peel, weighed, sliced, dried, crushed, pulverized, packed, labeled and stored. Having obtained the pumpkin flour, samples were sent to perform physical-chemical laboratories AGROLAB of Santo Domingo and Basic Chemistry Quevedo State Technical University. The results obtained in this study permitted the identification of treatment No. 2 (pumpkin mature x 60 º C x 24h) as the best, because he obtained better results in physical and chemical analysis. .....